2012
DOI: 10.5430/jnep.v2n3p66
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric and maternal sociodemographic assessment of the breastfeeding self-efficacy scale - short form in a brazilian sample

Abstract: Objectives: This study was developed to psychometrically assess the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) among women living in Fortaleza-CE-Brazil and to examine the relationship between breastfeeding self-efficacy and maternal demographic variables. Methods:This methodological study replicated the original psychometric assessment of the BSES-SF conducted in Canada. A convenience sample of 294 postpartum women were recruited.Results: The Cronbach's alpha coefficient for the BSES-SF was 0.74. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 24 publications
(33 reference statements)
8
39
1
18
Order By: Relevance
“…Similarly, no relationship was found between the scale score and maternal age in the others studies (1,4,6,12,13,15). However, the study by Dodt et al (2012) indicated a strong correlation (7). Not only the study by Dodt et al (2012), but also the one by Wutke and Dennis (2010) identified a weak correlation between the scale score and maternal age (2010) (7,13).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, no relationship was found between the scale score and maternal age in the others studies (1,4,6,12,13,15). However, the study by Dodt et al (2012) indicated a strong correlation (7). Not only the study by Dodt et al (2012), but also the one by Wutke and Dennis (2010) identified a weak correlation between the scale score and maternal age (2010) (7,13).…”
Section: Discussionmentioning
confidence: 89%
“…The initiative is a global effort to implement practices that protect, promote and support breastfeeding, so as to ensure that all maternity wards become centres for breastfeeding support. To be designated as 'baby-friendly,' it is necessary to refuse free or low-cost breast milk substitutes, feeding bottles or teats, and to have implemented the "10 steps to support successful breastfeeding" (7).…”
Section: Introductionmentioning
confidence: 99%
“…Women's counseling and skin-to-skin contact between mother and baby are the key light technologies that should be encouraged. In order to determine the needs of women in relation to breastfeeding and to promote personalized care, light-weight technologies such as the Breastfeeding Self-Efficacy Scale can be used, in its full or short form, both of which have already been adapted to the Brazilian context (19)(20) .…”
Section: Discussionmentioning
confidence: 99%
“…Sua versão reduzida, a Short Form (SF), com 14 itens, foi validada em estudo desenvolvido na região Nordeste do Brasil (DODT ET AL., 2012).…”
Section: Metodologiaunclassified
“…Quanto às variáveis obstétricas, há evidências de que o AM, e a sua duração, está associado: ao tipo de parto, crianças nascidas por cesariana eletiva apresentam risco de ser desmamadas precocemente (VIEIRA ET AL., 2015); aos nascimentos em hospitais que cumprem os Dez Passos para o Sucesso do Aleitamento Materno, onde se incentivam a amamentação, por meio da promoção, proteção e apoio ao aleitamento materno, e, de modo geral, aumentam a probabilidade de elas se manterem em Aleitamento Materno Exclusivo (AME) por mais tempo (MARGOTTI; EPIFANIO, 2014;PASSANHA ET AL., 2015;VIEIRA ET AL., 2015); ao número de filhos anteriores, pois a primiparidade está frequentemente associada à prática de desmame precoce (SALUSTIANO;DINIZ;ABDALLAH, 2012;SOUZA ET AL., 2012) que é um dos fatores de desnutrição e de altas taxas de mortalidade infantil (PRIMO;AMORIM;LIMA, 2004); ao número de consultas de pré-natal, pois mostram associação significativa com AME (ASEMAHAGN, 2016); ao apoio paterno no ato de amamentar, visto que o pai tem grande destaque no suporte e influência na decisão da mulher em amamentar e na sua continuidade (SALVADOR, 2012;SILVA;SANTIAGO;LAMONIER, 2012;TEWABE ET AL., 2017), e ao escore da Breastfeeding Self-Efficacy Scale (BSES), onde escores mais elevados obtidos por meio da Escala de Autoeficácia na Amamentação estão associados à amamentação exclusiva (GLASSMAN ET AL., 2014;MARGOTTI;EPIFANIO, 2014 união estável entre os pais (FROTA ET AL., 2016); mães com renda melhor são mais propensas a praticar AME e tendem a amantar mais seus filhos (TEWABE ET AL., 2017).…”
Section: Introductionunclassified